(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Because fatty acid binding proteins (FABPs) and peroxisome proliferator-activated receptor (PPAR) ? physically interact, the ability of FABPs to modulate lipid signaling could be exploited for developing medications, improving therapeutic or prophylactic measures for the control of metabolic disorders, and for controlling the activity of their therapeutic targets such as PPARs. Purpose: To examine PPAR?-mediated differences in energy substrate among type 2 diabetes mellitus (T2DM) patients differing in the stage of diabetic retinopathy. Material and Methods: This study involved 101 T2DM patients (101 eyes) with different stages of diabetic retinopathy (DR) and 40 non-diabetics (controls) who were comparable in age, gender and body mass index. DR was graded using the ETDRS scale. The polymorphism was detected by real-time PCR on a Real-Time Gene Amp® PCR System 7500 (Applied Biosystems). ELISA was used to determine serum L-FABP levels with Human L-FABP ELISA kit (Hycult Biotech). Conclusion: We found a significant variation in fatty acid (FA) concentrations in red blood cell membranes in T2DM patients differing in PPAR?-gene mediated phenotypes. Among wild-type carriers, arachidonic acid concentration increased 1.4-fold in those with the early stage of DR (р < 0.05) compared to controls and decreased 7.5-fold in those with DR progression (р < 0.05). Among carriers of the 12Ala allele, arachidonic acid concentration decreased twofold in those with the early stage of DR (р < 0.05) compared to controls, and further gradually decreased with DR progression. There was a gradual and not significant increase in L-FABP concentration with DR progression in T2DM patients carrying the wild genotype. Among carriers of the 12Ala allele, concentration of the chaperone increased fourfold in those with the early stage of DR compared to controls (р < 0.05), and gradually decreased with DR progression.